Trigo help!

posted by .

Ok, i've tried this question, and it brings me to no answers. Please help!

Prove the following:
secY(1+tanY)=6cosecY

my workings:
LeftHandSide:
secY + tanY/cosY
= 1/cosY + sinY/cos^2Y
=(cosY+sinY)/cos^2Y
= ???
How should i attempt this question?? Am i even on the right track? Please help, much appreciated!

  • Trigo help! -

    When I come across an unusual trig identity to prove, the first thing I do is try some arbitrary angle.
    Since it is an Identity it should be true for any angle
    e.g. Y = 30º
    LS = sec30(1+tan30) = appr. 1.821
    RS = 6csc30 = 12

    No wonder you can't prove it, it is not true !

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calc

    what is the derivative of sinx- cosy = 0 in its simplest form?
  2. Trigonometry

    Prove that (cosy/1+siny) + (1+siny/cosy) = 2secy
  3. Trigonometry

    Write equivalent equations in the form of inverse functions for a.)x=y+cos è b.)cosy=x^2 (can you show how you would solve) a.) x= y+ cos è cos è = x-y theta = cos^-1(x-y) b.) cosy=x^2 cos(y) = x^2 y = Cos^-1(x^2)
  4. Trigonometry (repost Reiny)

    at 1:35am I posted ; Write equivalent equations in the form of inverse functions for a.)x=y+cos theta b.)cosy=x^2 my answers were a.) x= y+ cos theta cos theta = x-y theta = cos^-1(x-y) b.) cosy=x^2 cos(y) = x^2 y = Cos^-1(x^2) your …
  5. Trigonometry(please Clarify)

    I posted before ; Write equivalent equations in the form of inverse functions for a.)x=y+cos theta b.)cosy=x^2 my answers were a.) x= y+ cos theta cos theta = x-y theta = cos^-1(x-y) b.) cosy=x^2 cos(y) = x^2 y = Cos^-1(x^2) your post …
  6. maths (trigonometry)

    please solve these if possible Q1. If sinx +siny=3(cosy-cosx) then the value of sin3x/sin3y. Q2. If sina ,cosa,and tan a are in g.p.then cos cubea+cos square a is equal to
  7. Trigonometry Help

    Simplify: sin(x-y)cosy+cos(x-y)siny = (sinxcosy-cosxsiny)cosy+(cosxcosy+sinxsiny)siny = ?
  8. Math

    Suppose f(x) = sin(pi*cosx) On any interval where the inverse function y = f –1(x) exists, the derivative of f –1(x) with respect to x is: a)-1/(cos(pi*cosx)), where x and y are related by the equation (satisfy the equation) x=sin(pi*cosy) …
  9. Math

    How do I get (sinx cosy + cosx siny) (cosx cosy + sinx siny) in the form of 1/2(sin2x + sin2y)?
  10. math

    (coty sec^2 y-coty)/(siny tany+cosy)

More Similar Questions